EFEKTIVITAS PENJATUHAN SANKSI TINDAKAN TERHADAP ANAK PELAKU TINDAK PIDANA DI PENGADILAN NEGERI PEKANBARU - Pasaribu, Bahagia Bagio; Artina, Dessy; Ferawati, Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Children are the mandate as well as the ultimate gift of God that we must always guardbecause in him the inherent dignity, dignity, and rights as human beings must be respected.Children are also the next generation of generation and successors of existing developmentstruggles and future generations of national ideals, and are entitled to survival and are entitled toprotection from acts of violence and discrimination and civil rights and freedom. However, manychildren violate living norms in society and become perpetrators of criminal acts. Every child whocommits a crime will be asked for the ability to be responsible because the child has violatedcriminal provisions, related to the ability to be responsible for the minimum responsibility forchildren that is currently at least - at least 12 years. In the case of imposing criminal sanctions onchildren who commit criminal acts, the basis of the judge is referring to Article 71 of Law Number11 of 2012 concerning the Child Criminal Justice System. In addition to being sentenced to criminalsanctions against children, sanctions can also be imposed as contained in Article 82 paragraph (1)of Law Number 11 of 2012 Child Criminal Justice System.The purpose of this thesis research is: first, to find out to find out the regulation of sanctionsfor actions against children in positive Indonesian law. Second to find out whether the effectivenessof taking action sanctions against child perpetrators of criminal offenses in the Pekanbaru DistrictCourt. types of empirical research or sociological legal research. Empirical juridical legalresearch or sociological legal research is research conducted directly at the site or in the field toobtain data to provide a complete and clear picture of the problem under study. This research wasconducted in the city of Pekanbaru, namely in the Class I A Pekanbaru District Court. The dataused are primary data, secondary data and tertiary data, data collection techniques usinginterviews and literature studies.Based on the results of the research and discussion it can be concluded that the first,Regulation of Sanctions Against Children in Indonesian Positive Law is regulated in the ChildCriminal Justice System Law also implements a double track system in imposing sanctions onchildren who are faced with the law, namely criminal sanctions and sanctions for action. Secondly,the effectiveness of imposing sanctions on the offender's child in Pekanbaru district court that thepunishment of children still has weaknesses in terms of stipulating sanctions for actions asregulated in the laws and regulations set out in the judge's decision. This can be seen from furtherguidelines in terms of determining sanctions for actions based solely on the convictions of judgesand not yet explicitly regulated and clearly the mechanism for determining sanctions for action.Suggestions, Regulation of Sanctions for Children needs to be regulated further so that in the futurein order to achieve the goal of conviction and provide certainty and benefit to perpetrators andvictims in this case the revision of the legislation on the juvenile justice system needs to be reviewedin relation to the criteria for sanctions for imposing sanctions the action against the child of theoffender in the pekanbaru district court can only be said to be effective if the regulation in the lawis implemented in the judge's decision so that there are guidelines in determining the criteria forsanctions for achieving the objectives of the punishment.Keywords: Effectiveness of the imposition of action sanctions on child offenders